Magnetic polymeric ionic liquid for both catalysis application and magnetic solid phase extraction approach - Behrooz Maleki; Reza Sandaroos; Fahimeh Yousefi; Milad Ghani; Sahar Peiman (Scientific Reports)
Abstract In this project, a new heterogeneous polymeric ionic liquid catalyst based on vinylimidazole, stabilized on magnetic nanoparticles )Fe3O4@Al2O3@[PBVIm]HSO4) was prepared. Then the desired catalyst was identified by TGA, FT-IR, VSM, and TEM techniques. The efficiency of this catalyst was measured in the synthesis of chromene, xanthene, and dihydropyrimidinone. Moreover, the capability of the prepared sorbent for the extraction and determination of BPA (bisphenol A) was studied. Under the optimum conditions, the linearity range of the technique was between 0.5 and 100 µg L−1 with the coefficient of determination (r2) of 0.9948. Relative standard deviations for intra- and inter-day precision for the BPA (bisphenol A) at 20 µg L−1 were in the range of 3.1–3.9% and 3.7–4.2%, respectively. The limit of detection and limit of quantification were 0.07 and 0.48 µg L−1 respectively. Excellent efficiency, compatibility with environmental conditions, and easy recycling of the catalyst are among the most important features of the synthetic catalyst.